The Relationships of Otolith Dimensions (Length-Breadth) with Weight and Total Length of Greater Forkbeard (Phycis blennoides (Brünnich, 1768)) Captured from northeastern Mediterranean Sea - Girgin, Hülya; Başusta, Nuri (Natural and Engineering Science, 2023)
The greater forkbeard, Phycis blennoides is captured by commercial trawler, has minor commercial value in Türkiye. This study is the first knowledge on otolith biometry-fish size relationships of Phycis blennoides living in the northeastern Mediterranean Sea. A total of 202 the greater forkbeard individuals were caught by commercial bottom trawl at a depth of 200 to 400 m in the northeastern Mediterranean. Minimum-maximum total length and weight of obtained fish specimens were found as 16.9-38.7 cm and 31.06-415.0 g for females and 16.3-38.3 cm and 27.14-504.08 g for males respectively. The difference of the total length and weight between the females and males of P. blennoides was statistically insignificant (P>0.05). The determination coefficient value showed that there were a moderate relationships between total length-right and left otolith lengths, total length-right and left otolith breadths. © 2023, Natural and Engineering Science. All rights reserved.
Keywords: Greater forkbeard; Iskenderun Bay; otolith biometry; Phycis blennoides